Pengaruh ROA, Proporsi Dewan Komisaris Independen, ACHANGE, LEV, DCHANGE Terhadap Tax Avoidance - Rahayu, Hesti; Cahyani, Ulriche Suci; Valeriyan, Gilbert Pius; Sinaga, Imelda; Purwati, Agnes Susana Merry (Disclosure: Journal of Accounting and Finance, 2024)
The background to this research focuses on several companies that carry out deliberate tax avoidance actions such as not remitting taxes that have been collected by not submitting Tax Returns (SPT). Tax avoidance or tax avoidance is an activity to reduce or eliminate tax debts that should be paid by the company by not violating existing laws. This study aims to detect whether there is a significant relationship between the independent variables in detecting tax avoidance in trading industry companies listed on the Indonesia Stock Exchange during the 2017-2021 period. This study uses a quantitative approach with sample data obtained from annual reports of trading industry companies that have been published on the Indonesia Stock Exchange during the 2017-2021 period.Â  The sample selection technique used was purposive sampling, and data was obtained from 30 samples. The method used is descriptive statistical analysis and multiple regression analysis. The results of this study indicate that the variables Return On Assets (ROA) and Pressure from Outside (LEV) have positive and significant results on tax avoidance. Other factors which include the Proportion of Independent Commissioners, Financial Stability (ACHANGE), and Change of Directors (DCHANGE) do not have a significant effect on tax avoidance.